(untitled) (Research, Society and Development, 2021)
The objective of this study to evaluate the effect of different HF concentrations and etching times on the microshear bond strength (μSBS) of LD to resin cement. Forty LD sections (8x8 mm) of 3-mm thickness were randomly distributed (n=10) in accordance with the HF concentration (5 or 10%) and surface etching time (20 or 60 sec). The specimens were silanized and received an air-thinned layer of a light-curable adhesive. Six translucent tubes (0.8-mm diameter and 1-mm height) were positioned over each LD section, filled with resin cement and light-cured. After 24 h of storage, the tubes were carefully removed and the specimens were submitted to the μSBS test. The results submitted to a two-way analysis of variance and Sidak post hoc test (α=.05). Representative HF-etched specimens and one non-etched LD specimen were observed under a field-emission scanning electron microscope. The interaction between the HF concentrations and etching times was not significant (p=0.075). No significant differences were observed regarding HF concentrations and etching times (p=0.06 and p=0.059, respectively). Surfaces of specimens etched with 10% HF for 60 sec were found with grooves and microcracks. The μSBS of LD to resin cement was not significantly influenced by different HF concentrations and etching times; however, the LD surface morphology was found considerably modified.